2022
DOI: 10.1177/00221678221124654
|View full text |Cite
|
Sign up to set email alerts
|

The CoVivre Program: Community Development and Empowerment to Address the Inequalities Exacerbated by the COVID-19 Pandemic in the Greater Montreal Area, Canada

Abstract: The COVID-19 pandemic had devastating effects around the world, yet it was not experienced equally by all. The emergence of the virus has been linked with the intensification of discrimination and inequities, as well as other systemic issues already present in society prior to the pandemic. The CoVivre Program was created with the mission to facilitate and accelerate initiatives aimed at reducing socioeconomic and health disparities caused by the COVID-19 pandemic in the Greater Montreal Area. CoVivre aims to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Relatedly, Gyu Park et al (2017) showed that empowering leaders not only positively influence employees' positive state of mind regarding their personal work and life but also enhances employees' psychological well-being and job engagement by developing their psychological capital. As per Schinazi et al (2022), empowerment can lead an individual to gain the confidence and strength to act upon one's life. Furthermore, recent research highlights the association of empowering leadership with both organizational innovation (Kim and Beehr, 2022;Naqshbandi et al, 2019;Supriyanto et al, 2023) and management innovation (Rohlfer et al, 2022).…”
Section: Leadership and Organizational Explorationmentioning
confidence: 99%
See 1 more Smart Citation
“…Relatedly, Gyu Park et al (2017) showed that empowering leaders not only positively influence employees' positive state of mind regarding their personal work and life but also enhances employees' psychological well-being and job engagement by developing their psychological capital. As per Schinazi et al (2022), empowerment can lead an individual to gain the confidence and strength to act upon one's life. Furthermore, recent research highlights the association of empowering leadership with both organizational innovation (Kim and Beehr, 2022;Naqshbandi et al, 2019;Supriyanto et al, 2023) and management innovation (Rohlfer et al, 2022).…”
Section: Leadership and Organizational Explorationmentioning
confidence: 99%
“…(2017) showed that empowering leaders not only positively influence employees’ positive state of mind regarding their personal work and life but also enhances employees’ psychological well-being and job engagement by developing their psychological capital. As per Schinazi et al. (2022), empowerment can lead an individual to gain the confidence and strength to act upon one’s life.…”
Section: Theoretical Framework and Hypothesesmentioning
confidence: 99%